ANALISIS IMPLEMENTASI NILAI-NILAI SILA PERSATUAN INDONESIA PADA MATA PELAJARAN PPKn SISWA KELAS X IPA SMA SANTUN UNTAN PONTIANAK - Yunika, Dayu; Mashudi, Mashudi; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is entitled Analysis of the Implementation of the Values of the Unity of Indonesian Unity in PPKn Subjects in Class X SMA Negeri 4 Pontianak. The problems in this study are 1) How is the understanding of grade X students of SMA SANTUN UNTAN Pontianak about the values of the Indonesian Unity precepts 2) How is the implementation of the values of the Indonesian Union precepts of class X students of SMA SANTUN UNTAN Pontianak 3) What are the attitudes of grade X high school students SANTUN UNTAN Pontianak against the values of the Indonesian Unity precepts. The purpose of this study is 1) To find out the extent of students' understanding of the values of the unity of Indonesian unity2) To find out how the implementation of the values of Indonesian Unity Sila grade X students of SMA SANTUN UNTAN Pontianak and 3) To find out how the attitude of students of class X SMA SANTUN UNTAN Pontianak against the values of Sila Persatuan Indonesia. The method of this research is descriptive qualitative with an observation guide tool and an interview guide with the author's own research instrument. The first data collection procedure in this study is to simplify the data based on written results in the field. After the data is arranged, the data is presented in the form of text and is narrative then the truth is checked again and after that the conclusion is drawn. Based on the results of this study the conclusionÂ Keywords: Implementation of Indonesian Unity Sila Values